MANAGEMENT STRATEGY OF ACEH GOVERNMENT SCHOLARSHIP PROGRAM IN BPSDM ACEH PROVINCE - DM Ismi Rizkiah; Tjahjo Suprayogo; Wangsih Wangsih; Dahlawi Dahlawi (Jurnal Scientia, 2023)
The Government of Aceh has invested in human resource development through the Human Resources Development Agency as the agency that has responsiblity for managing The Government of Aceh scholarships. Based on Aceh Governor Regulation Number 28 of 2019 about Aceh Government Scholarships, the scholarship aims to increase the capacity of reliable human resources in order to support the implementation of development in Aceh. During this program there were problems encountered such as the lack of optimal management process by the management and there is no such thing like a long-term Grand Design for the human development of Aceh. It needs to be followed up in achieving the goals that have been set on human development in Aceh. This study aims to analyze the management of Aceh Government scholarships managed by BPSDM Aceh and strategies carried out by BPSDM in managing scholarships. The research method used in this research is descriptive qualitative. The analysis tools used is SOAR analysis by doing a combination of matrices. Based on the results of SOAR analysis, there are 8 (eight) alternative strategies, such as providing scholarships in accordance with regional needs and right on target, making tracer studies for alumni, conducting periodic evaluations related to scholarship targets, making need assessments according to regional needs in distributing scholarships, developing human resources for scholarship management, improving scholarship management, providing opportunities to continue education and establishing cooperation with educational institutions at home and abroad in distributing scholarships. BPSDM is expected to improve the management of data on education needs for human resources to support Aceh development programs by making a Grand Design of Aceh human resources development so that the opportunities given to prospective scholarship recipients are in accordance with the needs and making tracer studies to find out alumni who have contributed to development in Aceh.